ANALISIS FAKTOR KEBERHASILAN PENGOBATAN TUBERCULOSIS DI WILAYAH KERJA PUSKESMAS NAMORAMBE - Novrika Silalahi; Afrilius Simanjuntak; Tedty Rohaya Tinambunan; Sulastri Ginting (Jurnal Penelitian Kesmasy, 2021)
Pulmonary tuberculosis is a chronic infectious disease that is one of the main health problems in the world. The indicator used as an evaluation of the treatment carried out is the success rate of treatment. There are many factors that influence the success of TB treatment. Lungs. This study uses an observational analytic research method with a research design using a retrospective cohort study approach with a sample of 44 people. The results of the analysis using the chi-square test with the results obtained indicate that medication adherence (p-value = 0.009<0.005) and RR of 6.857, the role of PMO (p-value = 0.019<0.005) and RR of 5.7, family support (p-value = 0.012 <0.005) and RR of 6.417, knowledge (p-value = 0.033 <0.005) and RR of 5.00 and all of these variables indicate there is a significant relationship with the success of treatment of patients with pulmonary TB.Paru at Puskesmas Namorambe